2005
DOI: 10.1097/00000542-200502000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Anesthesia Management Characteristics on Severe Morbidity and Mortality

Abstract: This article and its accompanying editorial have been selected for the Anesthesiology CME Program. After reading both articles, go to http://www.asahq.org/journal-cme to take the test and apply for Category 1 credit. Complete instructions may be found in the CME section at the back of this issue.Background: Quantitative estimates of how anesthesia management impacts perioperative morbidity and mortality are limited. The authors performed a study to identify risk factors related to anesthesia management for 24-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
117
2
17

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(139 citation statements)
references
References 51 publications
3
117
2
17
Order By: Relevance
“…All residents are trained to manage critical situations, such as difficult mask ventilation or intubation, and a manual crisis booklet is attached to all anesthesia machines. A study performed by Arbous et al [20] confirmed that the presence of two anesthetists instead of one decreases the risk of complications during emergent anesthesia, which is consistent with the findings of the present study. As we did not focus on the reasons of complications, we can only speculate about them.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…All residents are trained to manage critical situations, such as difficult mask ventilation or intubation, and a manual crisis booklet is attached to all anesthesia machines. A study performed by Arbous et al [20] confirmed that the presence of two anesthetists instead of one decreases the risk of complications during emergent anesthesia, which is consistent with the findings of the present study. As we did not focus on the reasons of complications, we can only speculate about them.…”
Section: Discussionsupporting
confidence: 93%
“…In their audit, Saito et al [8] stated that inappropriate speeds of drug injection are one of the reasons for errors in critical events, and these results indirectly support our speculations. [8,21] In addition, Arbous et al [20] found that compared with indirect availability, direct availability of the anesthesiologist during maintenance was associated with a significantly lower risk; in the present study, direct availability of the staff anesthesiologist was less during nighttime surgery, and this may be one of the reasons for increased risk of intraoperative complications.…”
Section: Discussionsupporting
confidence: 43%
“…Anaesthetic complications have been reported to increase ten-fold when reversal of neuromuscular block was omitted [12]. However, factors other than residual paralysis such as central respiratory depression due to residual effect of opioids and general anaesthetics may also contribute to CRE and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…A sua introdução na prática médica exige investimentos muito altos e em logo prazo, isto é, implicam pesquisas e experimentações que exigem, na maioria das vezes, grandes estruturas de laboratórios e qualidade de pesquisadores. Recentemente, foram publicados artigos levantando as causas de morbiletalidade em anestesia 1,2 . O mais recente 2 incluiu 869.483 pacientes e apontou, curiosamente, em uma lista de itens, que o coma ou os óbitos em 24 horas podem ser diminuídos, entre outros motivos, com cuidados com pessoal habilitado e presente ao ato anestésico, bem como com antagonismo de opióides e bloqueadores neuromusculares.…”
Section: A Revolução Na Anestesia Venosa: Sugammadex E Gantracuriumunclassified